2017
DOI: 10.1016/j.ijid.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a multidrug-resistant Citrobacter freundii ST8 harboring an unusual VIM-4 gene cassette in Poland

Abstract: All unusual gene cassettes containing VIM-DR (direct repeat) described thus far have been harbored by non-fermenters, i.e., Acinetobacter and Pseudomonas, underscoring the importance of resistance determinant mobility, which may go even beyond genus, family, and order boundaries. Great efforts need to be taken to explore pathways of resistance to 'last-resort' antimicrobials, especially among clinically relevant pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…The 76 STs from this study were compared with 171 STs from the Citrobacer MLST database, We found that 11 STs in this study shared the same sequence types with isolates from the database from other countries or regions or from different sources. Among these 11 STs, ST8 contained isolates from the urine of an acute myeloid leukemia patient from Poland (Majewski et al, 2017 ); ST12 contained isolates from a rectal swab; ST17 contained isolates from skin necrosis, urine and rectal swabs; ST30 contained isolates from fecal samples of diarrheal patients in our previous study (Liu et al, 2017a ); ST87, ST85, and ST45 each contained isolates from food in our previous study (Liu et al, 2017a ; ST116 contained isolates from blood; ST161 and ST166 contained isolates from water. Therefore strains of the same STs of C. freundii may be widely present in fecal, food, and other reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…The 76 STs from this study were compared with 171 STs from the Citrobacer MLST database, We found that 11 STs in this study shared the same sequence types with isolates from the database from other countries or regions or from different sources. Among these 11 STs, ST8 contained isolates from the urine of an acute myeloid leukemia patient from Poland (Majewski et al, 2017 ); ST12 contained isolates from a rectal swab; ST17 contained isolates from skin necrosis, urine and rectal swabs; ST30 contained isolates from fecal samples of diarrheal patients in our previous study (Liu et al, 2017a ); ST87, ST85, and ST45 each contained isolates from food in our previous study (Liu et al, 2017a ; ST116 contained isolates from blood; ST161 and ST166 contained isolates from water. Therefore strains of the same STs of C. freundii may be widely present in fecal, food, and other reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify the occurrence of CR in HM patients and to understand its epidemiology, we reviewed series and selected case reports that report colonization or infection of HM patients with CR bacteria. These studies were undertaken in different areas of the world, including New York, New Delhi, China, Stockholm, Frankfurt, Roma, Brescia, Athens, Ankara, Cairo, and Haifa in the series studies (Tables 1−3; Cattaneo et al, 2012Cattaneo et al, , 2018Kjellander et al, 2012;Schelenz et al, 2013;Satlin et al, 2013aSatlin et al, , 2016El-Mahallawy et al, 2014;Trecarichi et al, 2015Trecarichi et al, , 2016Wang et al, 2015Wang et al, , 2017Micozzi et al, 2017;Ballo et al, 2019), and in United States, Brazil, Spain, Italy, Poland, Turkey, Israel, Japan, China, and Austria in the case reports (Table 4; Muchtar et al, 2012;Carattoli et al, 2013;Chang et al, 2013;Satlin et al, 2013b;Girmenia et al, 2015;Huang et al, 2015;Kara Leitner et al, 2015;Xing et al, 2015;Kantarcioglu et al, 2016;Tofas et al, 2016;Zhang et al, 2016Zhang et al, , 2018Majewski et al, 2017;Piedra-Carrasco et al, 2017;Asai et al, 2018). When we geolocate the regions that have reported the presence of CR bacteria in HM patients in Figure 1, it can be observed that all these studies have been reported in regions that are either endemic or have a significant increase in carbapenemase enzymes (a coincidence with regions with high levels of CR bacteria) (Figure 1).…”
Section: Carbapenem Resistance In Hematological Patients Vs the Worlmentioning
confidence: 99%
“…When we compare this data with those related to the global distribution of carbapenemase worldwide, it is clear that the occurrence of the KPC enzyme in HM patients is related to its presence in the area (endemic or significant outbreak state) where the studies were conducted (China, Italy, Brazil, United States, Spain, Germany). Other carbapenemase enzymes have also been identified in CR bacteria isolated from HM patients, such as IMI (Huang et al, 2015), VIM (Majewski et al, 2017), or NDM (Carattoli et al, 2013;Zhang et al, 2018).…”
Section: Carbapenem Resistance In Hematological Patients Vs the Worlmentioning
confidence: 99%
“…C. freundii possesses an inducible AmpC β-lactamase, which can pose a challenge for antibiotic susceptibility reporting because an in vitro susceptibility may not correlate with clinical efficacy ( 2 ). With the general increase in the number of carbapenemase-producing Enterobacteriaceae , reports of carbapenemase-producing C. freundii have also increased ( 3 6 ). The main carbapenemases produced by Enterobacteriaceae belong to the Ambler class A (e.g., KPC), class B (e.g., IMP, VIM, and NDM) or class D (e.g., OXA-48 and its variants).…”
Section: Genome Announcementmentioning
confidence: 99%